(untitled) (Research, Society and Development, 2021)
The scope of this study is to analyze the decline of artisanal fishing in the municipality of Araguacema, Tocantins, in the Environmental Protection Area of Bananal/Canton Island, pointing out solutions for the sustainable use of fishing resources. The fishing production showed a decline, based on the records of the Z-05 Colony of Araguacema, where the average per fisherman was 102.44 ± 75.52 kg in 2015, 86.80 ± 59.81 in 2016, and 67.43 ± 38.95 in 2017. The drop in Capture per Effort Unit (CPUE) is an important indicator of decline in this period, especially the tucunaré (Cichla spp), a resource widely exploited in the region by artisanal and amateur fishermen. The monitoring of landings in a continuous manner should be a practice, as it gives greater reliability to the data collected. Fishery agreements can be a viable model of participatory management, as long as there is greater participation by governmental and non-governmental institutions.